STUDI FENOMENOLOGI TENTANG KESULITAN PERKALIAN DAN PEMBAGIAN PADA SISWA KELAS IV SDN JATISAMPURNA X - Indira Takiya Rahmayanti; Prayuningtyas Angger Wardhani; Fahrurozi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Difficulties in understanding multiplication and division continue to pose significant challenges in elementary mathematics learning. This issue negatively impacts students’ ability to master more complex material that relies on foundational knowledge of multiplication and division. This study aims to identify the types of difficulties experienced by fourth-grade students at SDN Jatisampurna X and to analyze the contributing factors. A qualitative approach with a phenomenological method was employed. Data were collected through observation, interviews, tests, and documentation. Data validity was ensured through source and technique triangulation. The data were analyzed using Miles and Huberman’s descriptive qualitative model, which includes data reduction, data display, and conclusion drawing. The results showed that only 41% of students met the Minimum Mastery Criteria (KKM). Most students struggled with basic arithmetic concepts, such as memorizing multiplication facts, applying columnar algorithms, and solving word problems. Common errors included reversed operation sequences, incorrect digit placement, and a lack of understanding of the “carrying” process. The contributing factors included weak conceptual understanding, low self-confidence, high dependency on teacher guidance, and insufficient frequency of independent practice. This study reveals technical misconceptions that are often overlooked and highlights the need for contextual and structured learning approaches to improve students’ comprehension.